STAT5 expression correlates with recurrence and survival in melanoma patients treated with interferon-α - Machiraju, Devayani; Gebhardt, Christoffer; Sucker, Antje; Buder-Bakhaya, Kristina; Schadendorf, Dirk; Hassel, Jessica C. (Melanoma research, 2018)
Interferons (IFN) have a direct growth-inhibiting effect on tumor cells through Janus kinase-dependent activation of the transcription factor signal transducer and activator of transcription (STAT1). In vitro, signaling through STAT5 has been demonstrated to counteract this effect and lead to IFN resistance of melanoma cell lines. In 32 patients treated with IFN-α in an adjuvant setting, we investigated paraffin-embedded tumor tissue from primary melanomas and melanoma metastases for expression of STAT3 and STAT5, by immunohistochemistry, and for expression of phosphorylated signaling transduction activating transcription factor (pSTAT)3 and pSTAT5, by immunofluorescence. Tumor cell expression levels of these proteins were correlated with patient characteristics and clinical outcomes. The patient cohort consisted of 12 (37.5%) patients at AJCC stage I/II (primary melanoma) and 20 (62.5%) at stage III/IV (metastatic melanoma). Recurrence was observed for 25 (78.1%) either during or after IFN-α therapy. χ Correlation of staining intensities with clinical data revealed association of pSTAT3 and STAT5 expression with sex (P=0.003 and 0.016, respectively) and of STAT3 with tumor stage (P=0.019). Recurrence of melanoma was found to be associated with high STAT5 expression (P=0.017). Multivariable regression analysis revealed STAT5 expression as an independent factor for predicting progression-free survival (P<0.0001) and overall survival (P=0.022). In summary, high expression of STAT5 correlated with melanoma recurrence and survival of patients treated with IFN-α in the adjuvant setting. Recently, it has been suggested that mutations of Janus kinases are involved in resistance to immune checkpoint blocker treatments implying a possible role of STAT5 for immune checkpoint resistance.
Gesehen am 09.09.2019
DOI vermutlich fehlerhaft